[OP.7C.03] KLOTHO GENE POLYMORPHISM INTERACTS WITH ADDUCIN-ENDOGENOUS OUABAIN-NA+-K+ ATPASE SYSTEM IN SALT SENSITIVE HYPERTENSION. (September 2016) - Tentori, S.; Lanzani, C.; Citterio, L.; Brioni, E.; Simonini, M.; Zagato, L.; Messaggio, E.; Manunta, P.
Abstract : Objective: The genetic basis of salt sensitive (SSH) hypertension consists in a very complex network of dynamic interaction among genetic-environmental factors that may change with aging. The existence of a regulatory genetic network (RGN) as triggering mechanism of SSH has been already postulated for Adducin-Endogenous Ouabain-Na+-K+ ATPase (ADD-EO-NKA) system. The observation that Klotho (KL) is a newly discovered aging suppressor gene can directly affect the Na+, K+-ATPase activity opening new possible interaction with the RGN. Aim of this study is to evaluate the interactions between Add-EO-NKA and KL genes on pressure-natriuresis relationship in SSH. Design and method: A large cohort of 655 naive hypertensive patients underwent acute Na Load test for phenotyping the pressure natriuresis relationship (PNat). Results: Univariate analysis showed significant interactions between Klotho G/T SNP and RGN network (SNPs in loci of ADDs, EO synthesis, metabolism, and activity) with PNat slope. Figure. No caption available. Furthermore, those patients carrying together mutate KL and NCX1 (SLC8A1) variants showed a rightward shit of PNat curve than in wild type condition. Similar differences are present in delta systolic BP (8.92 vs 2.26 mmHg), with lower fractional excretion of Na (FE Na 1.48 vs 2.40 %), and increased circulating EO (251.41 vs 190.75 pM) after Na load. Conclusions: Klotho beside its effects on Ca/P metabolism may influence renal sodium handling and vascular activity through different component of EO-ADD-NKA system.